RETAIL DEVELOPMENT IN THE BANKING SECTOR OF THE ECONOMY OF UKRAINE - Сідельник, Олена; Кошельник, Іванна (Socio-economic relations in the digital society, 2019)
The paper examines the essence of retail and substantiates that bank retail is the process of creating and selling an accessible, inclusive and understandable list of products and services provided by a banking institution for the maximum number of consumers who intend to obtain them. It is determined that in the conditions of functioning of the banking system, the basis for effective work of the bank is the formation and implementation of mechanisms, which should be oriented to create an effective system of sales of products and services, and to create the highest possible consumer value, as well as to form a holistic system of «client-bank» cooperation, that would provide effective communication between them. It is determined that in today`s conditions the effective activity and competitiveness of any commercial bank is to a greater extent ensured by the introduction of new, socially oriented services nby expanding the sphere of retail with the use of innovative technologies. The activity of Oschadbank JSC in the retail banking segment is analyzed, and it is substantiated that banking retail is actively developing in the directions of increasing the resource base in terms of attracting funds of the population, growth of consumer lending, growth of commission income under conditions of increase in the volume of transfers, payments for bills, payments through paycards, development of alternative and unconventional channels of sales of banking products. The paper determines that the development of banking in Ukraine is characterized by trends in the use of digital technologies and the universalization of financial and economic relations, therefore, under such conditions, promising directions for further development of banking retail in Ukraine are: further improvement of remote customer service; providing round- the-clock activities of the bank contact center; enhancing the efficient operation of the front office through the use of the Single Window system; partnerships between banking institutions and retail companies. The development of above-indicated promising areas will allow banking institutions to continue to cover almost all areas of the financial services market.
Keywords: retail; banking retail; banking products and services; innovative technologies